2015
DOI: 10.1155/2015/568363
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Outcome of Anterior Lamellar Reposition in Treating Trachomatous Trichiasis

Abstract: Purpose. To evaluate the outcome of anterior lamellar reposition (ALR) in treating trachomatous trichiasis. Methods. Patients with trachomatous trichiasis or entropion with short tarsus were treated by ALR between February 2009 and November 2013. This included splitting of the lid margin behind the aberrant lash line to separate the lid lamellae. The anterior lamella was recessed and fixated using 4/0 silk sutures. The extra lashes and their routes were excised. Sutures were removed by the 3rd week and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Regarding postoperative cosmesis, marginal thickening with abnormal appearance was noticed in all patients underwent ALR during the early postoperative period; however, this tends to soften with reversion to normal skin color within few weeks. Similarly, Ahmed and Abdelbaky 17 showed that most separated lid margins reverted to their normal color with upward remigration of anterior lamella within 3 months. The authors believe that preoperative counseling regarding possible poor cosmesis in the early postoperative period following ALR is important to reduce postoperative patient's anxiety.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…Regarding postoperative cosmesis, marginal thickening with abnormal appearance was noticed in all patients underwent ALR during the early postoperative period; however, this tends to soften with reversion to normal skin color within few weeks. Similarly, Ahmed and Abdelbaky 17 showed that most separated lid margins reverted to their normal color with upward remigration of anterior lamella within 3 months. The authors believe that preoperative counseling regarding possible poor cosmesis in the early postoperative period following ALR is important to reduce postoperative patient's anxiety.…”
Section: Figurementioning
confidence: 78%
“…16 In addition, the lid margin incision can be performed posterior to the more posterior aberrant eyelashes. 17 Anterior lamellar laxity with dermatochalasis was found in 4 patients with PTT who underwent ALR without repositioning sutures early in the study. However, the use of mattress sutures between lower lid retractors and anterior lamella has eliminated this complication in subsequent cases given the resultant anterior lamellar tightening.…”
mentioning
confidence: 94%
“…combined the original procedure with terminal tarsal rotation. [ 9 ] As previously discussed, other authors have reported lid crease incision and lifting the anterior lamella off the posterior with or without a GLS[ 4 5 6 ] the obvious advantage being avoidance of surgery to the conjunctiva and hence improve safety in conditions such as OCP. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…Anterior lamellar repositioning (ALR) is a well-known, simple, and widely popular method for treating both upper and lower eyelid cicatricial margin entropion. [ 1 2 3 4 5 6 ] Welsh[ 1 ] described ALR with grey-line split (GLS) and suture repositioning for correcting cicatricial entropion in 1969. Some other published techniques have added a lid crease incision with GLS to recess the levator.…”
mentioning
confidence: 99%
See 1 more Smart Citation